Analisa Gangguan Inlet Guide Vane Pada Gas Turbine Generator Tambak Lorok Menggunakan Metode Root Cause Failure Analysis - Prayudi Prayudi; Arie Wicaksono (JURNAL POWERPLANT, 2016)
IGV (Inlet Guide Vanes) is a component of the main supporters of a GTG (Gas Turbine Generator), IGV serves as a regulator of the flow rate of air entering the compressor when heading to the GTG start up and during operation. In operation there is the possibility of interference with the IGV that can make the performance of GTG decreased or even the most fatal trip can download the GTG. Problematic sources of interference from an IGV can come from various sources. To determine what resources are causing problematic function of IGV required an analysis method that is able to parse problems / disorders that actually happened. The method used is RCFA (Root Cause Failure Analysis), RCFA an analysis method that is able to break down the root cause of the occurrence of a problem / nuisance. By using the method RCFA expected problems can be resolved with due diligence and it is possible to not reappear at a later time.